Calculation of two-photon absorption by nanocrystals of CsPbBr3 - Blundell, S. A. (2021)
We present calculations of the two-photon absorption cross section σ(2)(ω) for nanocrystals (NCs) of the inorganic perovskite CsPbBr3 for photon energies ω ranging from the absorption threshold at 2ω≈2.3eV up to 2ω=3.1eV. The calculations employ a 4×4k⋅p envelope-function model, with final-state excitons described in a self-consistent Hartree-Fock approximation. The k⋅p corrections to σ(2)(ω) are found to be rather large, giving a reduction of about 30% in the cross section at the largest energies considered. The cross section is shown to be independent of polarization in the effective-mass approximation (EMA), but including k⋅p corrections leads to a small difference in σ(2)(ω) between circular and linear polarization, which rises to about 16% at 2ω=3.1eV. The theoretical cross section follows closely a power-law dependence on NC size, σ(2)(ω)∝Lα, with theoretical exponents α=3.4 (EMA) or α=3.2 (4×4k⋅p model), in excellent agreement with experiment. The dominant contribution to the exponent α is shown to be the number of final-state excitons per unit energy. Measured values of the absolute (normalized) cross section σ(2)(ω) show a large spread of values, differing by as much as a factor of 25 for some NC sizes. Our calculations strongly favor a group of measurements at the lower end of the reported range of σ(2)(ω).